Penerapan Etika Bisnis Islam Dalam Mengungkap Keuntungan Usaha - Nani Hamdani Amir; Nur Nilawati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine in depth how mixed traders apply the principles of Islamic business ethics, particularly in the aspect of Honesty in disclosing business profits, which can contribute to achieving blessings in profits. This study uses a descriptive qualitative approach with a focus on 20 mixed traders using a purposive sampling technique. Data collection techniques were carried out through interviews, observation, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The results show that this study aims to examine the implementation of Islamic business ethics principles in trading practices, particularly in terms of profit disclosure. Principles such as monotheism, balance, free will, responsibility, and truth become the moral foundation in trading activities that not only pursue material profits, but also blessings as a form of happiness in this world and the hereafter. The findings show that although most traders have not implemented a formal record-keeping system, they have informal mechanisms tailored to their capabilities. Disclosure of profits is done contextually and reflects the values of justice ('adl), trustworthiness, and benefit ( al-maslahah ). In addition, traders tend to set reasonable profit margins to maintain customer satisfaction. This reflects the integration between spiritual values and economic practices in realizing Islamic business ethics that are just and sustainable.